Membrane scaling in osmotically driven membrane processes - Zhang, Minmin (2016)
Water shortage is a serious problem that has impelled many industries and researchers to investigate new access to clean and safe drinking water. Osmotically driven membrane processes, such as forward osmosis (FO) and pressure retarded osmosis (PRO) as emerging technologies for freshwater production, have attracted more research interests and applications. However, scaling is still a significant challenge in both FO and PRO application and has not yet been fully addressed in the literature. The unique phenomena in osmotically driven membrane processes (e.g., internal concentration polarization (ICP) and reverse solute diffusion (RSD)) and their effects on FO and PRO scaling require further investigation in order to provide a mechanistic understanding of FO and PRO scaling. Therefore, the work aims to systematically study the effect of water chemistry and operational conditions on FO and PRO scaling.